Presidential Leadership : politics and policy making - Edwards, George C.; Mayer, Kenneth R., 1960-; Wayne, Stephen J. (Lanham, Maryland : Rowman & Littlefield, 2023)
"With a focus on presidential leadership, the authors address the capacity of chief executives to fulfill their tasks, exercise their powers, and utilize their organizational structures to affect the output of government. This text examines all aspects of the presidency, up to and including the administration of President Joe Biden"
Includes bibliographical references and index.
Keywords: Presidents -- United States